2002
DOI: 10.1177/1357633x0200800507
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Minimization Analysis of Orthopaedic Consultations Using Videoconferencing in Comparison with Conventional Consulting

Abstract: We compared the costs of conventional outpatient visits to the surgical department of the University Hospital of Oulu with those of videoconferencing between the primary care centre in Pyhäjärvi and the University Hospital (separated by 160 km). The cost data were obtained from a randomized controlled trial that included 145 first-admission and follow-up orthopaedic patients. In the telemedicine group the annual fixed costs were 6074 in the hospital and 3910 in the primary care centre. The additional variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 15 publications
2
74
1
Order By: Relevance
“…Another Finnish study had similar results. Wider utilization of the VC equipment for other purposes, or the use of less expensive VC equipment, would make services cost-saving even at relatively short distances [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another Finnish study had similar results. Wider utilization of the VC equipment for other purposes, or the use of less expensive VC equipment, would make services cost-saving even at relatively short distances [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence showed that the use of videoconferencing could be a useful educational tool in clinical and biomedical sciences, especially in underserved areas 8‐11 . Other evidence showed that the use of videoconferencing could be cost‐effective 12 . In pharmacy education, previous evidence showed that the use of videoconferencing in academia APPE elective was effective and successful 13 .…”
Section: Discussionmentioning
confidence: 99%
“…1 In-home telerehabilitation, defined as the provision of remote rehabilitation services to individuals with persistent and significant disabilities through information technologies and telecommunications in their home, 2 is growing as a complementary or alternative intervention to traditional face-to-face therapy in home care and outpatient services. 3 In rehabilitation, teleconsultation between two healthcare services has been studied with patients requiring speech therapy, 2,4-11 mental health, 12 and physical assessments such as for wounds, [13][14][15] orthopedic, [16][17][18] and neurologic conditions 19 and for assistive devices adjustment. [20][21][22] Moreover, two studies investigated the accuracy of teleassessment in the field of telerehabilitation.…”
Section: Introductionmentioning
confidence: 99%